2019
DOI: 10.1063/1.5081730
|View full text |Cite
|
Sign up to set email alerts
|

Excitation-tailored dual-color emission of manganese(II)-doped perovskite nanocrystals

Abstract: Manganese(II)-doped perovskite nanocrystals with superior dual-color light emission properties are promising for optoelectronic applications. Here, we report that the emission color of these nanocrystals can be tailored by continuous-wave excitation because of the saturation of dopant emission at a record low light density ($10 mW/cm 2). By detuning the repetition rates of excitation laser sources, we show that the bottleneck of exciton-manganese(II) energy transfer caused by the imbalanced excitation and deex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 50 publications
0
29
2
Order By: Relevance
“…The maximum PLQY of their best sample was about 27% with a Mn‐doping concentration of 1.3%, and the excited‐state decay of the Mn emission at 585 nm exhibited a long lifetime of about 1.4 ms, which is a typical timescale for Mn emission in d–d transition. [ 70 ] Ghosh et al and Wang et al nearly simultaneously reported the temperature‐dependent variation of emission intensity and emission wavelength of both host PNCs (CsPbCl 3 ) and Mn dopants ranging from tens of kelvin to more than 300 K. [ 71,72 ] They observed the blue shift of the emission peak position with the increasing temperature (Figure 3f,g), attributed to the interplay between the electron–phonon renormalization and the thermal expansion. Ghosh et al found that the PL intensity of Mn 2+ diminishes with the increasing temperature up to 125 K, due to the thermal quenching induced by the thermal ionization of optically excited carriers.…”
Section: Doping‐induced Dual‐color Emission In the Uv‐vis Rangementioning
confidence: 99%
“…The maximum PLQY of their best sample was about 27% with a Mn‐doping concentration of 1.3%, and the excited‐state decay of the Mn emission at 585 nm exhibited a long lifetime of about 1.4 ms, which is a typical timescale for Mn emission in d–d transition. [ 70 ] Ghosh et al and Wang et al nearly simultaneously reported the temperature‐dependent variation of emission intensity and emission wavelength of both host PNCs (CsPbCl 3 ) and Mn dopants ranging from tens of kelvin to more than 300 K. [ 71,72 ] They observed the blue shift of the emission peak position with the increasing temperature (Figure 3f,g), attributed to the interplay between the electron–phonon renormalization and the thermal expansion. Ghosh et al found that the PL intensity of Mn 2+ diminishes with the increasing temperature up to 125 K, due to the thermal quenching induced by the thermal ionization of optically excited carriers.…”
Section: Doping‐induced Dual‐color Emission In the Uv‐vis Rangementioning
confidence: 99%
“…Through the layer‐by‐layer assembly, multifunctional micromotors could be manufactured at micron size in an easy way, which provides more space for active micro‐design to meet different applications. [ 73 ] Biology in nature also provides excellent biomaterials for the design of microrobots. Xu et al.…”
Section: The Core Capabilities and Technical Components Of Microrobots For Active Drug Deliverymentioning
confidence: 99%
“…As a natural active drug carrier, especially for diseases in the female reproductive tract, the sperm cells exhibited a high drug encapsulation capability and drug‐carrying stability, conveniently minimizing toxic side effects and unwanted drug accumulation in healthy tissues. [ 73 ]…”
Section: The Core Capabilities and Technical Components Of Microrobots For Active Drug Deliverymentioning
confidence: 99%
See 2 more Smart Citations